1996
DOI: 10.1093/jpepsy/21.5.735
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Distress Among Caregivers to Children with Chronic Medical Conditions

Abstract: Explored informant differences and assessed the importance of sociodemographic factors, child health status characteristics, and caregiver burden to variability in psychological symptoms among caregivers to 116 children with chronic medical conditions. Important informant effects were found. Caregiver-reported, but not physician-reported, burden was an important predictor. Severity of illness, whether rated by physician or caregiver, had little predictive effect whereas child impairment predicted greater distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
2
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 20 publications
5
93
2
8
Order By: Relevance
“…Nesse sentido, a baixa incidência de práticas coercitivas no grupo crônico, revelada no presente estudo, tenderia a trazer benefícios para o desenvolvimento da criança com doença crônica. Todavia, vários estudos apontam que essas crianças teriam maior probabilidade de desenvolver problemas de comportamento do que crianças sem problemas de saúde (Canning, 1996;Heller et al, 1985). Embora a incidência de problemas de comportamento não tenha sido aqui examinada, é possível que os problemas de comportamento entre crianças com doença crô-nica estejam mais associados à permissividade dos pais também decorrente dos problemas de saúde da criança, do que à utilização de práticas coercitivas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Nesse sentido, a baixa incidência de práticas coercitivas no grupo crônico, revelada no presente estudo, tenderia a trazer benefícios para o desenvolvimento da criança com doença crônica. Todavia, vários estudos apontam que essas crianças teriam maior probabilidade de desenvolver problemas de comportamento do que crianças sem problemas de saúde (Canning, 1996;Heller et al, 1985). Embora a incidência de problemas de comportamento não tenha sido aqui examinada, é possível que os problemas de comportamento entre crianças com doença crô-nica estejam mais associados à permissividade dos pais também decorrente dos problemas de saúde da criança, do que à utilização de práticas coercitivas.…”
Section: Discussionunclassified
“…Hopkins, Roizen, Lindsay e Carrol (1995) encontraram em crianças com atresia de vias biliares, um tipo de doença hepática congênita, maiores riscos com relação ao temperamento, já que as deficiênci-as nutricionais que acompanham a doença podem causar irritabilidade. Em crianças com fibrose cística foram encontrados altos índices de problemas de comportamento em pesquisa que incluía mais de uma enfermidade no grupo clínico (Canning, 1996). De modo análogo, o estudo de Heller, Rafman, Zvagulis e Pless (1985) evidenciou que as crianças portadoras de enfermidades congênitas, como, por exemplo, doenças cardíacas, apresentavam significativamente mais problemas de comportamento do que o grupo controle de crianças sem problemas de saúde.…”
unclassified
See 1 more Smart Citation
“…One way to understand the negative impact of children's chronic conditions on parents' lives is through the concept of the burden of caregiving, which is defined as a caregiver's perceived responsibilities and limitations that are inflicted upon the self and the family (Canning, Harris, & Kelleher, 1996). For parents of chronically ill children, the tasks of parenting and caregiving go hand in hand as these parents are also the main informal health caregivers.…”
Section: Description Parents' Qol In the Context Of Pediatric Health mentioning
confidence: 99%
“…Parental caregiving for children with chronic health conditions is a complex experience, encompassing both negative and positive dimensions, such as caregiving burdens and uplifts (Green, 2007;Larson, 2010). While the deleterious effects of caregiving burden on parents' adaptation outcomes are documented in pediatric literature for chronic medical conditions in general (Canning, Harris, & Kelleher, 1996), and for asthma in particular (Crespo, Carona, Silva, Canavarro, & Dattilio, 2011;Fiese, Wamboldt, & Anbar, 2005), the associations between caregiving uplifts and adaptation outcomes remain a neglected research topic. Even if some authors have suggested a positive impact of perceived benefits of caregiving on parents' emotional and physical health (Green, 2007), and some evidence has been gathered for the buffering effect of caregiving uplifts on the associations between caregiving burden and parents' quality of life (QoL) when caring for a child with a disability (Carona, Pereira, Moreira, Silva, & Canavarro, 2013), the examination of the role of positive coping strategies on these parental adaptation processes has not been yet conducted.…”
mentioning
confidence: 99%